Learning Process Understanding ICT Use Learning Satisfaction to Improve Learning in the Classroom - Razak, Fathul (ALACRITY : Journal of Education, 2024)
The aim of this research is to explain and determine the influence of the Learning Process variables, Understanding the Use of ICT and Learning Satisfaction on Learning Improvement both partially and simultaneously. This research uses a qualitative descriptive approach. The results of partial hypothesis testing calculations obtained a value of tcount > ttable or 5.618 > 1.978 and the significance obtained was 0.000 < 0.05, meaning that partially the Learning Process had a positive and significant effect on Learning Improvement. The results of partial hypothesis testing calculations obtained a value of tcount > ttable or 4.539 > 1.978 and the significance obtained was 0.000 < 0.05, meaning that partially understanding the use of ICT had a positive and significant effect on improving learning. The results of partial hypothesis testing calculations obtained a value of tcount > ttable or 2.5658 > 1.978 and the significance obtained was 0.011 < 0.05, meaning that partially Learning Satisfaction had a positive and significant effect on Learning Improvement.